Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4269/ajtmh.20-1177
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics, Ventilator Management, and Clinical Outcome in Patients Receiving Invasive Ventilation in Intensive Care Units from 10 Asian Middle-Income Countries (PRoVENT-iMiC): An International, Multicenter, Prospective Study

Abstract: Epidemiology, ventilator management, and outcome in patients receiving invasive ventilation in intensive care units (ICUs) in middle-income countries are largely unknown. PRactice of VENTilation in Middle-income Countries is an international multicenter 4-week observational study of invasively ventilated adult patients in 54 ICUs from 10 Asian countries conducted in 2017/18. Study outcomes included major ventilator settings (including tidal volume [V T ] and positive end-expiratory pressure [PEEP]); the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
3
23
1
Order By: Relevance
“… 9 , 12 , 16 , 17 A similar use of protective mechanical ventilation has been reported from Asian middle-income countries. 24 In accordance with existing information for ARDS not related to COVID-19, 25 driving pressure was strongly associated with mortality, which is a novel finding.…”
Section: Discussionsupporting
confidence: 81%
“… 9 , 12 , 16 , 17 A similar use of protective mechanical ventilation has been reported from Asian middle-income countries. 24 In accordance with existing information for ARDS not related to COVID-19, 25 driving pressure was strongly associated with mortality, which is a novel finding.…”
Section: Discussionsupporting
confidence: 81%
“…The lung injury prediction score performs poorly in predicting ARDS, as also suggested by one validation study 24 and subsequent investigations. 16,21,35 However, we cannot exclude the possibility that ARDS was underdiagnosed in ICUs in MICs. Although, physicians in MICs seem to recognise ARDS equally well or even better than those in HICs, 9,36 some ICUs might not have the resources to apply the Berlin definition for ARDS such as chest x-ray imaging and blood gas analysis.…”
Section: Table 3: Clinical Outcomes According To the Economic Groupmentioning
confidence: 96%
“…4 In the PRoVENT-iMIC study performed in Asia, which reported availability of diagnostic tools, x-ray apparatuses and blood gas analysers were available for over 90% of centres, although the resources were often shared with the hospital and not dedicated to the ICU. 21 LUNG SAFE was the only study to use an additional algorithm-based tool to identify patients who fulfilled the Berlin definition of ARDS. 13 Although notable differences were found in demographics and comorbidities, there was neither a difference in diseases severity on ICU admission, nor in the practice of ventilation, between HICs and MICs.…”
Section: Table 3: Clinical Outcomes According To the Economic Groupmentioning
confidence: 99%
“…However, measuring the PaO 2 is not always possible or could be too costly to use in resource–limited settings. While in some middle–income countries arterial blood gas measurements are increasingly available, [ 5 ] access is far from universal in critical care facilities worldwide [ 6 , 7 ]. In a recent report on COVID-19 in African ICUs, in only 82% of the participating hospitals there was a possibility to perform blood gas analyses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%